1-Butyl-3-methylimidazolium bromide functionalized zeolites: nature of interactions and catalytic activity for carbohydrate conversion to platform chemicals. Issue 9 (4th August 2020) - Yedla, Santosh Kumar; Velaga, Bharath; Choudhury, Souradip; Namdeo, Ashutosh; Golder, Animes Kumar; Peela, Nageswara Rao
Abstract : In this study, 1-butyl-3-methylimidazolium bromide ([BMIM]Br) functionalized zeolites were synthesized by a facile ship-in-bottle strategy and utilized for the carbohydrates conversion to platform chemicals (5-hydroxymethylfurfural and furfural). Abstract : In this study, 1-butyl-3-methylimidazolium bromide ([BMIM]Br) functionalized zeolites were synthesized by a facile ship-in-bottle strategy. The interactive effects between [BMIM]Br and zeolites were studied in detail to explore their synergy in catalyzing the reaction of carbohydrate conversion to specific platform chemicals (5-hydroxymethylfurfural (5-HMF) and furfural). The functionalized zeolites were characterized thoroughly using various techniques to determine the [BMIM]Br presence and its effect on zeolite properties. The [BMIM]Br in functionalized zeolites decomposed in two stages and possessed higher thermal stability compared to its bulk counterpart. The decomposition temperature of the IL varies with the zeolite framework type and cation. The increase in the electron density at the oxygen and aluminum sites affected the bond angle of –[Si–O–Al]– as observed from XPS and 27 Al SS-NMR. Varying degrees of electrostatic interaction existed between [BMIM]Br and the zeolite, as revealed by XPS, XRD, BET, and TGA. Over [BMIM]Br/NaY, the highest 5-HMF yield of 80, 62, and 59% and a furfural yield of 77% were obtained from fructose, glucose, and cellulose, and xylose, respectively. Stabilization of 5-HMF was apparent with all the [BMIM]Br functionalized zeolites, which prevented the side product formation. The 5-HMF yield was higher by a factor of 2 with the functionalized zeolites as compared to that with their bare zeolite counterparts. Moreover, [BMIM]Br/NaY showed good recycling stability.